2015
DOI: 10.1021/acs.jpcb.5b04757
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive PDMAEMA Brushes: Effect of Gold Nanoparticle Deposition

Abstract: The paper addresses the effect of gold nanoparticle (Au-NP) deposition on the thermoresponsive volume phase transition of the weak polyelectrolyte poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) brushes. PDMAEMA brushes were synthesized via surface-initiated atom transfer radical polymerization (SI-ATRP). The PDMAEMA/Au-NP composite brushes were fabricated by immersing the brush modified wafer in the Au-NP suspension. Atomic force microscopy (AFM), ellipsometry, and scanning electron microscopy (SEM) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…[22][23][24] The pioneering work of Okano and co-workers in this area, who exploited PNIPAM brushes as a workhorse system, has been more recently expanded to included brushes of PNIPAM-co-poly-(oligoethylene glycol) methacrylate (POEGMA), POEGMAco-PDEGMA, poly(MEO 2 MA 50 -co-HOEGMA 20 -co-HEMA 30 ), poly(dimethylaminoethyl methacrylate), and poly[tri-(ethylene glycol) ethyl ether methacrylate]. [1,[25][26][27][28] Homopolymer brushes that exhibit a lower critical solution temperature (LCST) in the vicinity of physiological temperatures are scarcer. Poly(di(ethylene glycol)methyl ether methacrylate) (PDEGMA) possesses a bulk LCST of 26 °C, which is increased in brushes to 32 °C, is known to afford cell and protein resistant coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The pioneering work of Okano and co-workers in this area, who exploited PNIPAM brushes as a workhorse system, has been more recently expanded to included brushes of PNIPAM-co-poly-(oligoethylene glycol) methacrylate (POEGMA), POEGMAco-PDEGMA, poly(MEO 2 MA 50 -co-HOEGMA 20 -co-HEMA 30 ), poly(dimethylaminoethyl methacrylate), and poly[tri-(ethylene glycol) ethyl ether methacrylate]. [1,[25][26][27][28] Homopolymer brushes that exhibit a lower critical solution temperature (LCST) in the vicinity of physiological temperatures are scarcer. Poly(di(ethylene glycol)methyl ether methacrylate) (PDEGMA) possesses a bulk LCST of 26 °C, which is increased in brushes to 32 °C, is known to afford cell and protein resistant coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] The responsiveness of these brushes was utilized to design surfaces with tunable wetting properties with regard to adhesion, adsorption, friction, and other properties. [19][20][21][22][23][24][25][26][27][28][29][30][31] In one approach for the design of stimuli-responsive brushes, the switching is provided by changing the properties (charge and hydrophobicity) of the polymer themselves. [32,33] This example includes the switching of the adhesion of cells on thermoresponsive poly(N-isopropylacrylamide) (PNIPAM) brushes.…”
Section: Doi: 101002/macp201900030mentioning
confidence: 99%
“…They are also able to demonstrate switchable properties due to the stimuli‐responsive behavior of the polymer chains that were grafted onto the surface . The responsiveness of these brushes was utilized to design surfaces with tunable wetting properties with regard to adhesion, adsorption, friction, and other properties . In one approach for the design of stimuli‐responsive brushes, the switching is provided by changing the properties (charge and hydrophobicity) of the polymer themselves .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some reports have demonstrated that PDMAEMA can act as both reducing agent and stabilizer simultaneously in the formation of gold nanoparticles, [21][22][23][24] based on the fact that Poly (2-(dimethylamino) ethyl methacrylate) (PDMAEMA) is a hydrophilic polymer with temperature and pH sensitivities, excellent biocompatibility, and a well-studied environmentally responsive polymer. 25 Such an approach greatly simplified the preparation and purification of gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%